Proceedings of the 13th Annual ACM International Conference on Mobile Computing and Networking 2007
DOI: 10.1145/1287853.1287862
|View full text |Cite
|
Sign up to set email alerts
|

Designing localized algorithms for barrier coverage

Abstract: Global barrier coverage that requires much fewer sensors than full coverage, is known to be an appropriate model of coverage for movement detection applications such as intrusion detection. However, it has been proved that given a sensor deployment, sensors can not locally determine whether the deployment provides global barrier coverage, making it impossible to develop localized algorithms, thus limiting its use in practice.In this paper, we introduce the concept of local barrier coverage to address this limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
136
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(137 citation statements)
references
References 13 publications
0
136
0
1
Order By: Relevance
“…We consider a default sensing range of R s i = 30 m for all of the sensors [31]. A two-ray ground path loss model with γ = 4 and g 0 = 8.1 ·10 −3 [32] is considered.…”
Section: Simulation Environmentmentioning
confidence: 99%
“…We consider a default sensing range of R s i = 30 m for all of the sensors [31]. A two-ray ground path loss model with γ = 4 and g 0 = 8.1 ·10 −3 [32] is considered.…”
Section: Simulation Environmentmentioning
confidence: 99%
“…In addition, they consider barrier coverage with high probability when sensors are deployed randomly. In [4] the problem of local barrier coverage is introduced and it is shown that it is possible for individual sensors to locally determine the existence of local barrier coverage, even when the region of deployment is arbitrarily curved. Techniques for deriving density estimates for achieving barrier coverage and connectivity in thin strips are introduced in [1], where sensors are deployed as a barrier to detect moving objects and events.…”
Section: Related Workmentioning
confidence: 99%
“…In addition, they consider barrier coverage with high probability when sensors are deployed randomly. The problem of local barrier coverage is introduced in [4]. It shows that it is possible for individual sensors to locally determine the existence of local barrier coverage, even when the region of deployment is arbitrarily curved.…”
Section: Related Workmentioning
confidence: 99%